International Financial Reporting Standards and Their Effect on Global Supply Chain Dynamics - Eri Kusnanto; Muhammad Rizal (International Journal of Management, Accounting & Finance (KBIJMAF), 2024)
Global supply chain dynamics have been profoundly impacted by the implementation of International Financial Reporting Standards (IFRS), which have improved openness, decreased information asymmetry, and fostered strong governance and accountability frameworks. This qualitative assessment of the literature seeks to combine contemporary empirical research with theoretical viewpoints to investigate the complex effects of IFRS on supply chain management. This study employs a qualitative methodology, evaluating academic articles, case studies, and theoretical papers. It has been discovered that the implementation of IFRS enhances the quality of financial reporting, hence promoting improved decision-making, supplier selection, and risk management. Standardizing finance procedures encourages cooperation and confidence among supply chain participants, which improves operational resilience and efficiencies. The analysis comes to the conclusion that the implementation of IFRS has a significant beneficial effect on supply chain management worldwide, fostering resilience and efficiency through enhanced financial procedures.